2020
DOI: 10.1186/s40360-020-00445-y
|View full text |Cite
|
Sign up to set email alerts
|

5-Hydroxytryptamine-3 receptor antagonist and dexamethasone as prophylaxis for chemotherapy-induced nausea and vomiting during moderately emetic chemotherapy for solid tumors: a multicenter, prospective, observational study

Abstract: Background Of patients receiving moderate emetic risk chemotherapy (MEC), 30–90% experience chemotherapy-induced nausea and vomiting (CINV); however, the optimal antiemetic treatment remains controversial. Methods In this multicenter, prospective, observational study of adults treated with MEC while receiving chemotherapy for various cancer types in Japan, the enrolled patients kept diaries documenting CINV. All participants received a 5-hydroxytryptamine-3 receptor antagonist and dexamethasone. Results Of… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 12 publications
0
14
0
Order By: Relevance
“…Various studies had shown that female and nondrinker has a high risk of CINV, and carboplatin combination chemotherapy has a low control rate in prevention CINV in gynecologic cancer [13,17,18] . In addition, the median age of the patients in this study is 62 years old, researches about prevention of CINV suggested that control rate increases along with the age of the patients, age of 65 and younger is one of the risk factors may explain the lower TC rate in this study [13,19] . Again, another reason that could explain the comparatively lower TC rate in this study is due to the prevalence of the immune checkpoint inhibitors in recent years, Arbour et al reported that corticosteroid lowers the therapeutic effect of such medications [20] .…”
Section: Discussionmentioning
confidence: 70%
“…Various studies had shown that female and nondrinker has a high risk of CINV, and carboplatin combination chemotherapy has a low control rate in prevention CINV in gynecologic cancer [13,17,18] . In addition, the median age of the patients in this study is 62 years old, researches about prevention of CINV suggested that control rate increases along with the age of the patients, age of 65 and younger is one of the risk factors may explain the lower TC rate in this study [13,19] . Again, another reason that could explain the comparatively lower TC rate in this study is due to the prevalence of the immune checkpoint inhibitors in recent years, Arbour et al reported that corticosteroid lowers the therapeutic effect of such medications [20] .…”
Section: Discussionmentioning
confidence: 70%
“…CINV in patients receiving CBDCA+PTX can be controlled relatively well by two antiemetics [8,15]. Ito et al [8] reported that the CBDCA+PEM regimen had relatively high emetic potential, and triple antiemetic therapy with a 5-HT3 receptor antagonist, DEX, and aprepitant may be an effective prophylactic treatment in patients receiving the CBDCA+PEM regimen.…”
Section: Discussionmentioning
confidence: 99%
“…We analyzed pooled data of 240 patients from two multicenter, prospective, observational studies. Individual study results were previously published [14,15]. The patient selection flowchart is shown in Fig.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several antiemetic agents have been developed such as 5-hydroxytryptamine-3 receptor antagonists (5-HT 3 RAs) and the neurokinin-1 receptor antagonist (NK-1 RA) aprepitant (Apr). Consensus guidelines [3][4][5][6] for the prophylaxis of CINV are primarily based on the emetogenic potential of chemotherapy. However, moderately emetogenic chemotherapy (MEC) agents have a broad range of emetogenicity (30-90%) relative to that of agents categorized by other emetogenic risks.…”
Section: Introductionmentioning
confidence: 99%